IMPACTO DEL CRECIMIENTO ECONÓMICO INDUSTRIAL SOBRE LOS RECURSOS ENERGÉTICO E HÍDRICO EN COSTA RICA - Díaz Sánchez, Luisa M. (2012)
An empirical relationship between water consumption, energy consumption and industrial GDP was established, for the case of Costa Rica. This relationship may be useful in predicting the pressure exerted on natural resources by the effects derived from growth of GDP. These predictions will make possible to establish public and sectorial policies related to water and energy management, and assesses the sector in order to achieve the national goal of carbon neutrality by 2021. Additionally, indicators of energy intensity (7,1 ± 0,5) TJ / million dollars of GDPi), water intensity ((1,0 ± 0,4) 10 5 m3 / million dollars of GDPi) and carbon intensity (217 CO2 kg equivalent / million dollars of GNP i) for the industrial sector of Costa Rica were established and could be used as reference for environmental assessment of the industrial sector in the future. *** Palabras clave: indicador de intensidad energética; indicador de intensidad hídrica; intensidad de carbono; elasticidad hídrica y energética